1992
DOI: 10.1111/j.1365-246x.1992.tb04638.x
|View full text |Cite
|
Sign up to set email alerts
|

The 1971 May 12 Burdur earthquake sequence, SW Turkey: a synthesis of seismological and geological observations

Abstract: S U M M A R YIt is now widely accepted that the rapid extension observed in western Turkey is mainly accommodated by large active normal faults which control the geomorphology. The NE-SW trending Burdur, Acigol and Baklan basins bounded by large faults form a system of half-graben whose orientation is evident in both the topography and the tilting of Neogene sediments adjacent to them.We used long-period Pand SH-waveforms t o determine the source parameters of the two largest earthquakes of the 1971 May 12 seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(97 citation statements)
references
References 27 publications
3
90
0
4
Order By: Relevance
“…This basin is the continuation of the Pliny trench. This interpretation, strongly supported by marine geophysical data (ten Veen et al, 2004), precludes an alternative interpretation in which the Pliny trench is related to the hypothetical FBFZ, a correlation previously suggested by several authors (Taymaz and Price, 1992;Barka et al, 1997;Temiz et al, 1997;ten Veen et al, 2004). The FBFZ and RTF are evaluated as a wide left lateral fault zone with a large component of extension and well-defined seismicity (Taymaz et al, 1991;Taymaz and Price, 1992;McClusky et al, 2000McClusky et al, , 2003Gürer et al, 2004;Nyst and Thatcher, 2004;Reilinger et al, 2010;Çevikbilen and Taymaz, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…This basin is the continuation of the Pliny trench. This interpretation, strongly supported by marine geophysical data (ten Veen et al, 2004), precludes an alternative interpretation in which the Pliny trench is related to the hypothetical FBFZ, a correlation previously suggested by several authors (Taymaz and Price, 1992;Barka et al, 1997;Temiz et al, 1997;ten Veen et al, 2004). The FBFZ and RTF are evaluated as a wide left lateral fault zone with a large component of extension and well-defined seismicity (Taymaz et al, 1991;Taymaz and Price, 1992;McClusky et al, 2000McClusky et al, , 2003Gürer et al, 2004;Nyst and Thatcher, 2004;Reilinger et al, 2010;Çevikbilen and Taymaz, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…In contrast to that the Holocene sedimentary sequences are not crossed by strike-slip faults in either Çameli or any other graben, latter authors have attributed these structural features to the youngest (Holocene) deformation. Whereas, both the focal mechanism solutions of destructive earthquakes (Table 1 and Figure 1(b)) sourced from the margin-boundary active faults of grabens and the kinematic analyses of slip-plane data measured on them (Figure 24) altogether obviously reveal that the Holocene deformation in the northern section of the IA is related to the tensional neotectonic regime and related normal faulting, not compressive neotectonic regime and related strike-slip faulting (Altuncu et al, in press;Kılıç & Utkucu, 2012;Tan, Tapırdamaz, & Yörük 2008;Taymaz & Price, 1992;Wright et al, 1999; KOERI (http://www.koeri.boun.edu.tr/); EMSC, http://www.emsc-csem.org/#2).…”
Section: Discussionmentioning
confidence: 99%
“…This seismic event moved the northeastern section of the Burdur normal fault, which is the northeastern margin-boundary fault of the Burdur graben, and led to development of 23 km long ground surface rupture with the 1.5 m vertical displacement on the northern hanging wall block (Pınar & Lahn, 1952). Even though, in some of previous works (Akyüz & Altunel, 2001;Alçiçek et al, 2006;Altunel et al, 2000;Eyidoğan & Barka, 1996;Karaman, 2010;Temiz, Poisso, Andrieux, & Barka, 1997;Verhaert, Muchez, Keppens, & Sintubin, 2009;Wright et al, 1999;Yağmurlu et al, 1997), it has been reported that the NE-trending Burdur fault is a neotectonic structure in the nature of sinistral strike-slip fault forming the northeastern onshore continuation of the Pliny trench, along which an oblique subduction is lasting, the fault plane solution diagrams of the Guidoboni et al (1994) and Altunel et al (1999) instrumental period earthquakes (Kılıç & Utkucu, 2007;Taymaz & Price, 1992; KOERI, http://www.koeri.boun. edu.tr/) obviously indicated that the sources of these earthquakes are oblique-slip normal faults not strike-slip faulting, and the northern section of the IA is under the control of a tensional neotectonic regime, not a compressive tectonic regime (Figures 1(b)).…”
Section: Seismicity Of Northern Section Of Iamentioning
confidence: 99%
See 1 more Smart Citation
“…From the Turkish side the broader region of occurrence is dominated by the presence of the transtensional left-lateral Fethiye -Burdur Fault Zone (FBFZ). It is a well known structure of pronounced NE-SW trending faults and basins, which roughly align between the cities of Fethiye and Afyon (Taymaz and Price, 1992;Ocakoğlu, 2012). These faults are combined with N-S faults, to form an en-echelon basin configuration, which continues westward into the eastern Hellenic Arc.…”
Section: Introductionmentioning
confidence: 99%